Measurement model for video usage among tesl pre-service teachers in Institute of Teacher Education Malaysia (ITEM): Exploratory and confirmatory analyses. - A Rahmat, Rohaida; Saidi, Siti Bahirah; Mohd Nasir , Nazatul Syima (Journal of Islamic, Social, Economics and Development, 2024)
Video provides learners with a truly authentic learning experience, a lot of videos which are shared online contain different cultural value, it brings real-life values as in customs, beliefs, sports, and food, these can build stronger context to the learners. However, the use of video would also restrict the potential of learning among the students, as they would rather search for the answer online. This study was conducted to investigate the use of Tiktok and students’ perception of writing essay. Using a survey design, this study provides perceptions about: a) the use of video in Institute of Teacher Education Malaysia (ITEM) among TESL pre-service teachers in Malaysia.